Base Site Approach on Urban Tourist Movement in Quality and Sustainable Tourism Destinations - Muhamad Muhamad; Endah Nurhawaeny Kardiyati; AB Ahmad; Nur Imam Khabibi (International Journal of Architecture and Urbanism, 2026)
This study aims to examine the pattern of tourist movement with the Base Site approach on urban tourist attractions in the urban center of Yogyakarta city and explore tourist motivations and characteristics of tourist destinations. Method of analysis used in this study is quantitative descriptive. The results showed that the pattern of tourist movement in urban tourist attractions in the center of Yogyakarta formed a tourist travel route with a single point, base site, stopover pattern. The results showed that according to the route and movement of tourists, they visited a maximum of 2 tourist destinations while traveling. The movement and travel routes of tourists are based on tourist motivation and conditions of tourist attractions visited, such as the location of adjacent tourist attractions, length of travel, road network conditions, and availability of public transportation modes. The conclusion is that the movement and routes of tourists visited in the core area of Yogyakarta city are based on the proximity of the distance and the types of tourist attractions on the visual linkage.